2020
DOI: 10.3390/molecules25173806
|View full text |Cite
|
Sign up to set email alerts
|

Workflow for the Quantification of Soluble and Insoluble Carbohydrates in Soybean Seed

Abstract: Soybean seed composition has a profound impact on its market value and commercial use as an important commodity. Increases in oil and protein content have been historically pursued by breeders and genetic engineers; consequently, rapid methods for their quantification are well established. The interest in complete carbohydrate profiles in mature seeds, on the other hand, has recently increased due to numerous attempts to redirect carbohydrates into oil and protein or to offer specialty seed with a specific sug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…The high reducing sugar content of RB1 might come from soluble soybean polysaccharide, a water-soluble fraction extracted from the cell wall material of the cotyledons of soybean [ 18 ]. In addition, it has been reported that the main soluble carbohydrates in soybean seeds are sucrose and the raffinose family of oligosaccharides (RFO), raffinose, and stachyose [ 19 ]. Since the soluble carbohydrate had been dissolved in the first soaking, the sugar concentration was lower in the second soaking and boiling.…”
Section: Resultsmentioning
confidence: 99%
“…The high reducing sugar content of RB1 might come from soluble soybean polysaccharide, a water-soluble fraction extracted from the cell wall material of the cotyledons of soybean [ 18 ]. In addition, it has been reported that the main soluble carbohydrates in soybean seeds are sucrose and the raffinose family of oligosaccharides (RFO), raffinose, and stachyose [ 19 ]. Since the soluble carbohydrate had been dissolved in the first soaking, the sugar concentration was lower in the second soaking and boiling.…”
Section: Resultsmentioning
confidence: 99%
“…Soluble sugars, hemicellulose and cellulose from mature soybean seed and immature embryos (24, 30, 33,36, 42, and 48 DAP) were quantified as described in Moretti et al . (2020).…”
Section: Methodsmentioning
confidence: 99%
“…It has been hypothesized that carbon derived from lipid and protein turnover contributes to RFOs synthesis during the late seed maturation stage. A 10-15% reduction in lipids coincides with RFOs accumulation during seed maturity ( Moretti et al., 2020 ). A protracted buildup of lipids without a reduction in protein content was also seen in recent research employing fast neutron-mutagenized soybean populations with deletions in genes involved in the central carbon metabolism ( Kambhampati et al., 2019 ).…”
Section: Strategies To Reduce Rfos Content In Plants For Nutritional ...mentioning
confidence: 99%